2015
DOI: 10.1038/srep09006
|View full text |Cite
|
Sign up to set email alerts
|

Fast discharge process of layered cobalt oxides due to high Na+ diffusion

Abstract: Sodium ion secondary battery (SIB) is a low-cost and ubiquitous secondary battery for next-generation large-scale energy storage. The diffusion process of large Na+ (ionic radius is 1.12 Å), however, is considered to be slower than that of small Li+ (0.76 Å). This would be a serious disadvantage of SIB as compared with the Lithium ion secondary battery (LIB). By means of the electrochemical impedance spectroscopy (EIS), we determined the diffusion constant (D) of Na+ in thin films of O3- and P2-type NaCoO2 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 24 publications
1
57
2
Order By: Relevance
“…In the as-grown film, intense 003 H and 006 H reflections are observed, indicating the 001-orientation of the films. We confirmed that the lattice constant c (=15.6 Å) of the as-grown film is consistent with the value (=15.58698(11) Å [9]) of the O3 phase. In the 2.3 V and 1.5 V films, the corresponding reflections shift to the low-2θ side, indicating widening of the interlayer distance.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…In the as-grown film, intense 003 H and 006 H reflections are observed, indicating the 001-orientation of the films. We confirmed that the lattice constant c (=15.6 Å) of the as-grown film is consistent with the value (=15.58698(11) Å [9]) of the O3 phase. In the 2.3 V and 1.5 V films, the corresponding reflections shift to the low-2θ side, indicating widening of the interlayer distance.…”
Section: Introductionsupporting
confidence: 73%
“…With use of the ideal capacity, we converted the discharge capacity into x and plotted the value on the upper axis. The capacity of the O3-NaCoO 2 film slightly decreases with increase in the discharge rate, even at ∼1C [9]: 116 mAh/g at 0.2C, 100 mAh/g at 1.2C, and 82 mAh/g at 12C. Then, the x value may be slightly overestimated.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Reproduced with permission. [ 34 ] Copyright 2015, Nature Publishing Group. Potentiostatic intermittent titration technique (PITT) plot (left) and evolution of diffusion coeffi cient (D) with depths of discharge (right) of e) Na 0.73 CoO 2 and f) Na 0.60 Ca 0.07 CoO 2 , respectively.…”
Section: (4 Of 38)mentioning
confidence: 99%
“…In Figure 4b, specific energies of TFCN achieved in 2-4.2 V as a function of the C-rate are plotted with those of other O3-NaMO 2 for comparison. 4,9,10,[19][20][21] TFCN indeed exhibits superior electrochemical performance: the specific energies achieved are 504 Wh/kg at C/20 and 200 Wh/kg at 30 C, outperforming many O3-NaMO 2 compounds.…”
mentioning
confidence: 99%